(3YdhjGJ eMeO Hf adGM GdMSjfj GdcGXejs - (3eMeO Hf adGM GdMSjfj GdcGXej,J (B1220 (3g` s
(3ChdgG (B:s
(3bGd jeOM CejQ GdeDefjf Ydjg GdSdGe, hjPcQ HYV eG hQO ajg ef GdbQBf hGdMOjK, hJSei GdcQGQjI(B: (3gjaGA cGO GdoZUf ojTHg bqOgG dh Cfg HGdMrdj CHgi eKeQ s
(3BNQgG (B:s
(3Udi GdEdg Ydjce hYdjg eG MeO Gdegjef Ph GdfhGd heG oOYj s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B132s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B47 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(278) s
Keywords: (3GdCOHs